Surface Morphology of Fe(III)-Porphyrin Thin Layers as Characterized by Atomic Force Microscopy - Utari Utari; Kusumandari Kusumandari; Budi Purnama; Mudasir Mudasir; Kamsul Abraha (Indonesian Journal of Chemistry, 2016)
Surface morphology of Fe(III)–porphyrin thin layers was studied using atomic force microscopy. The thin layer samples used in these experiments were deposited by spin coating methods on indium–tin-oxide substrates at room temperature under atmospheric conditions. Variations of thin layer of Fe(III)-porphyrin were done by modifying the rotational speed and the concentration of the solution. The experimental results demonstrated that the Fe(III)–porphyrin layers were observed as discrete nanomolecular islands. Both the number of nano-islands and thickness of the layer increased significantly with increasing concentration. A layer thickness of 15 nm was obtained for low concentrations of 0.00153 M and become 25 nm for dense concentrations of 0.153 M. Conversely, the higher number of islands were deposited on the surface of the substrate at a lower rotational speed.